The role of sphingolipids in neuronal plasticity of the brain. Issue 4 (15th March 2016) - Sonnino, Sandro; Prinetti, Alessandro
Abstract : This Editorial highlights a study by Müller et al . in which the authors suggest a new sphingolipid‐dependent mechanism for behavioral extinction. Their study should be considered in the broad perspective of sphingolipid metabolic pathways and traffic (depicted in the graphic). Read the highlighted article 'A sphingolipid mechanism for behavioral extinction' on page589 . Abstract : This Editorial highlights a study by Müller et al . in which the authors suggest a new sphingolipid‐dependent mechanism for behavioral extinction. Their study should be considered in the broad perspective of sphingolipid metabolic pathways and traffic (depicted in the graphic). Read the highlighted article 'A sphingolipid mechanism for behavioral extinction' on page589 .